Analysis of Performance Based Budgeting Implementation at the Plantation and Livestock Service Office of West Kalimantan Province - Papu, Tarsisius (Lembaga Publikasi Ilmiah Nusantara, 2025)
The purpose of this study was to determine how to apply performance-based budgeting and to find out what factors affect the application of performance-based budgeting in the Plantation Service of West Kalimantan Province. This study uses performance indicators and value for money to measure the performance of an organization. The data used is primary data obtained from the West Kalimantan Provincial Plantation Service in the Finance section in the form of Government Agency Performance Accountability Reports (LAKIP) and other related documents which are then analyzed descriptively to present a complete picture of the social setting or the relationship between the phenomena tested. Based on the Value For Money Calculation, the results show that the West Kalimantan Provincial Plantation Service has shown economic, efficient and effective performance.